Optimization of islamic education management of independent preacher based on the qur'an at Ma'had Aly Ki Bagus Hadikusumo Sukoharjo - Yetty Faridatul Ulfah; Ngatmin Abbass; Barik Pradana As-Syifa'; Faruq Abdillah; Ali Mutaqiin; Ahmad Mulalic (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to examine the implementation of Al-Qur'an-based Islamic education management at Ma'had Aly Ki Bagus Hadikusumo Sukoharjo, especially in forming Independent Preacher who are able to overcome the challenges of the times. The research method was a case study with a qualitative approach, through participatory observation, in-depth interviews, and document analysis. Observations were taken through the da'wah (preaching) development strategy carried out by Ma'had Aly Ki Bagus Hadikusumo and the objects of the researcher's interviews were leaders, administrators and Dai (Preachers), while documentation studies were obtained from references and literature related to the focus of the study. The results of the study indicate that the concept of Independent Dai, which combines da'wah expertise and economic independence, has made a positive contribution to the spiritual and economic development of the community. Islamic education management, namely integrated da’wah which includes planning, organizing, directing, and supervision has effectively produced professional and competent preachers. This study proposes the adoption of the concept of Independent Dai and effective management of Al-Qur'an-based da'wah by other Islamic educational institutions, to improve the quality of da'wah and strengthen the role of Islam in facing the challenges of materialism and individualism in modern society.